2023
DOI: 10.1111/imr.13235
|View full text |Cite
|
Sign up to set email alerts
|

Ferroptosis in immunostimulation and immunosuppression

Abstract: SummaryFerroptosis is a form of iron‐dependent regulated cell death characterized by the accumulation of toxic lipid peroxides, particularly in the plasma membrane, leading to lytic cell death. While it plays a crucial role in maintaining the overall health and proper functioning of multicellular organisms, it can also contribute to tissue damage and pathological conditions. Although ferroptotic damage is generally recognized as an immunostimulatory process associated with the release of damage‐associated mole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 114 publications
0
8
0
Order By: Relevance
“…Recent studies have indicated that ferroptosis‐related genes influence cancer development by affecting immunosuppression and infiltration of immune cells such as macrophages, CD4 + T cells, and CD8 + T cells 136,137 . Ferroptosis is known to induce and enhance immune responses by releasing intracellular contents, such as damage‐associated molecular patterns (DAMPs) 138–140 . Additionally, ferroptosis contributes positively to antitumor immunity.…”
Section: Ferroptosis In Gcmentioning
confidence: 99%
“…Recent studies have indicated that ferroptosis‐related genes influence cancer development by affecting immunosuppression and infiltration of immune cells such as macrophages, CD4 + T cells, and CD8 + T cells 136,137 . Ferroptosis is known to induce and enhance immune responses by releasing intracellular contents, such as damage‐associated molecular patterns (DAMPs) 138–140 . Additionally, ferroptosis contributes positively to antitumor immunity.…”
Section: Ferroptosis In Gcmentioning
confidence: 99%
“…The formal adoption of the term "Ferroptosis" in 2012 helped categorize this iron-dependent, non-apoptotic death pathway [ 131 ]. Notable morphological changes during ferroptosis include alterations in mitochondria, such as decreased cristae, denser membranes, and rupture, alongside lipid peroxidation, increased ROS, and the modulation of ferroptosis-specific genes [ 132 134 ].…”
Section: Introductionmentioning
confidence: 99%
“…[ 6 , 7 , 8 ] However, some in vivo studies have reported that stimulation of ferroptosis can promote certain types of cancers. [ 9 , 10 , 11 ] The variable characteristics of the tumor immune microenvironment stimulated by ferroptotic cancer cells may account for the inconsistent outcomes when using ferroptosis as a target for cancer therapy. [9] For example, when GPX4 is suppressed in liver cancer, ferroptotic cancer cells activate the myeloid‐derived suppressor cells to boost tumor growth, [10] and induction of ferroptosis by H 2 O 2 in pancreatic cancer cells facilitates the polarization of tumor‐promoting pro‐resolution M2‐like macrophages.…”
Section: Introductionmentioning
confidence: 99%
“…[ 9 , 10 , 11 ] The variable characteristics of the tumor immune microenvironment stimulated by ferroptotic cancer cells may account for the inconsistent outcomes when using ferroptosis as a target for cancer therapy. [9] For example, when GPX4 is suppressed in liver cancer, ferroptotic cancer cells activate the myeloid‐derived suppressor cells to boost tumor growth, [10] and induction of ferroptosis by H 2 O 2 in pancreatic cancer cells facilitates the polarization of tumor‐promoting pro‐resolution M2‐like macrophages. [12] In contrast, ferroptosis enhances the antitumor immune reaction due to inhibition of GPX4 in triple‐negative breast cancer, [13] and cancer cells undergoing ferroptosis lead to efficient antitumor immunity when vaccinated into tumor‐bearing mice.…”
Section: Introductionmentioning
confidence: 99%